2011
DOI: 10.1007/s10812-011-9440-y
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectra of associates of heterogeneous dye molecules in polymer matrices

Abstract: The formation processes for heterogeneous associates of cationic dyes in polyvinyl alcohol films are investigated. The influence of colorless anions on the heterogeneous association efficiency is established. The structures of heterogeneous dimers of various dyes in polymer matrixes are defined.Introduction. Polymeric laser elements that are both solutions of dyes [1] and polymeric matrices with incorporated molecules [2, 3] have recently become of great interest. The generating properties of such media are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Rhodamine 6G (Rh6G) is a strongly fluorescent and stable dye from xanthene group of well-defined concentration-dependent spectroscopic properties in solutions, polymer matrices or glasses. Therefore, it is a perfect model molecule for aggregation and energy transport studies. It has been found that at high Rh6G concentrations its fluorescent dimers or higher order aggregates may appear, but the susceptibility to dimerization and optical properties of these aggregates are strongly different depending on the solution or matrix properties.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodamine 6G (Rh6G) is a strongly fluorescent and stable dye from xanthene group of well-defined concentration-dependent spectroscopic properties in solutions, polymer matrices or glasses. Therefore, it is a perfect model molecule for aggregation and energy transport studies. It has been found that at high Rh6G concentrations its fluorescent dimers or higher order aggregates may appear, but the susceptibility to dimerization and optical properties of these aggregates are strongly different depending on the solution or matrix properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use the sol–gel process to obtain and study concentration-dependent fluorescence properties of rhodamine 6G entrapped in titanium dioxide (Rh6G/TiO 2 ) and silicon dioxide (Rh6G/SiO 2 ) nanolayers. Rh6G is a strongly fluorescent dye, the photophysical properties of which have been thoroughly studied at different concentrations in solutions, polymer matrices, glasses, and nanocomposites over past years using mostly steady-state spectroscopic methods. In particular, some recent studies of concentration-dependent behavior of Rh6G revealed that its dimers formed in viscous solutions or rigid media can be fluorescent. In many recent studies devoted to sol–gel derived luminescent materials, optically and physically thick samples have been prepared and measured. Such results, although very interesting, can be distorted by the presence of inner filter effects (reabsorption and reemission).…”
Section: Introductionmentioning
confidence: 99%